Association between chronic obstructive pulmonary disease and systemic inflammation: a systematic review and a meta-analysis. Issue 7 (28th June 2004) - Gan, W Q; Man, S F P; Senthilselvan, A; Sin, D D
Abstract : Background: Individuals with chronic obstructive pulmonary disease (COPD) are at increased risk of cardiovascular diseases, osteoporosis, and muscle wasting. Systemic inflammation may be involved in the pathogenesis of these disorders. A study was undertaken to determine whether systemic inflammation is present in stable COPD. Methods: A systematic review was conducted of studies which reported on the relationship between COPD, forced expiratory volume in 1 second (FEV1 ) or forced vital capacity (FVC), and levels of various systemic inflammatory markers: C-reactive protein (CRP), fibrinogen, leucocytes, tumour necrosis factor-α (TNF-α), and interleukins 6 and 8. Where possible the results were pooled together to produce a summary estimate using a random or fixed effects model. Results: Fourteen original studies were identified. Overall, the standardised mean difference in the CRP level between COPD and control subjects was 0.53 units (95% confidence interval (CI) 0.34 to 0.72). The standardised mean difference in the fibrinogen level was 0.47 units (95% CI 0.29 to 0.65). Circulating leucocytes were also higher in COPD than in control subjects (standardised mean difference 0.44 units (95% CI 0.20 to 0.67)), as were serum TNF-α levels (standardised mean difference 0.59 units (95% CI 0.29 to 0.89)). Conclusions: Reduced lung function is associated with increased levels of systemic inflammatory markers which may have important pathophysiological and therapeutic implications for subjects with stable COPD.